2013
DOI: 10.1039/c2tb00228k
|View full text |Cite
|
Sign up to set email alerts
|

Protein free microcapsules obtained from plant spores as a model for drug delivery: ibuprofen encapsulation, release and taste masking

Abstract: Sporopollenin exine capsules (SEC) extracted from Lycopodium clavatum spores were shown to encapsulate ibuprofen as a drug model, with 97 AE 1% efficiency as measured by recovery of the loaded drug and absence of the drug on the SEC surface by scanning electron microscopy (SEM). The encapsulated ibuprofen was shown to be unchanged from its bulk crystalline form by solid state NMR, FTIR and XRD. Essential for drug delivery applications, SEC were shown to be non-toxic to human endothelial cells and free of aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 45 publications
5
97
1
1
Order By: Relevance
“…Our results with natural spores support previous studies using exine capsules, which indicate the lack of a barrier to retard macromolecule release in SGF and SIF for a longer period of time. [ 7,16,18 ] Similar drug release profi les were reported with the use of processed sporopollenin microcapsules extracted from L. clavatum spores. [ 16,18 ] To explore the structural changes after FITC-conjugated BSA release in PBS, we performed CLSM after complete release and Adv.…”
Section: Modulating Macromolecules Release From Natural Sporesmentioning
confidence: 52%
See 1 more Smart Citation
“…Our results with natural spores support previous studies using exine capsules, which indicate the lack of a barrier to retard macromolecule release in SGF and SIF for a longer period of time. [ 7,16,18 ] Similar drug release profi les were reported with the use of processed sporopollenin microcapsules extracted from L. clavatum spores. [ 16,18 ] To explore the structural changes after FITC-conjugated BSA release in PBS, we performed CLSM after complete release and Adv.…”
Section: Modulating Macromolecules Release From Natural Sporesmentioning
confidence: 52%
“…[30][31][32] Most conventional techniques used for encapsulation such as emulsion solvent evaporation, spray drying, and chemical conjugation fail to reliably provide either size monodispersity or well-defi ned microstructures. [ 26,27,[30][31][32] Although several studies have reported the use of empty exine microcapsules for the encapsulation of drugs, vaccines, and magnetic resonance imaging (MRI) contrast agents, as well as for use in cosmetics and food supplements, [ 7,[16][17][18]22 ] the use of the natural "spores" as a microencapsulation material and delivery vehicle still remains unexplored. In this regard, we have directed our efforts toward exploring systems to produce macromoleculeloaded spores using three different microencapsulation techniques.…”
Section: Doi: 101002/adfm201502322mentioning
confidence: 99%
“…Any protein in the raw material is eradicated during the extraction to produce allergen free, non-toxic shells [20]. …”
Section: Introductionmentioning
confidence: 99%
“…After this process, the cells still remain viable within the chamber and the exines undamaged, which further illustrate the remarkable elasticity and physical robustness of the exines. The potential for sporopollenin exines to be used in food and pharmaceutical applications has been demonstrated by their having taste-masking properties to the tongue when encapsulated with, such as fish oil and ibuprofen (Diego-Taboada et al, 2013). Also, the exines were shown to encapsulate a commercial gadolinium(III) MRI contrast agent and allow slow release over 8 h in blood plasma (Lorch et al, 2009).…”
mentioning
confidence: 99%
“…Also, the exines were shown to encapsulate a commercial gadolinium(III) MRI contrast agent and allow slow release over 8 h in blood plasma (Lorch et al, 2009). In vitro studies have shown exines to have the potential to act as an effective drug delivery vector in which release can be triggered by pH (Beckett et al, 2009;Diego-Taboada et al, 2013).…”
mentioning
confidence: 99%